Stock Return and Trade Volume Analysis of Selected Indian Cement Companies' Stocks - Sharma, Dr.Vikas; Sharma, Dr. Pooja; Pathak, Dr. Nitin (The journal of contemporary issues in business and government, 2022)
This work aims to analyze stock return, Trade volume of select cement companies in India. Ten cement companies are selected based on high market capitalization. www.nse.india.com was used to gather information. Investors, stakeholders, and policymakers all pay close attention to the return of stock and volume analysis. Some previous study shows that there is no relationship between stock return and volume, while others show that there is. The beta, correlation, and Granger causality tests are used by researchers to analyses stock return and volume. The beta value of all firms reveals which stocks are worth investing in. The correlation result clearly reveals that stock return and volume have a positive relationship, but the relationship between stock volume and value is the strongest. The causality test, on the other hand, verifies the same conclusion.